God is Back : how the global revival of faith is changing the world - Micklethwait, John.; Wooldridge, Adrian (New York : Penguin Press, 2009)
On the street and in the corridors of power, religion is surging worldwide. From Russia to Turkey to India, nations that swore off faith in the last century--or even tried to stamp it out--are now run by avowedly religious leaders. This book examines this new world, from exorcisms in São Paulo to religious skirmishing in Nigeria, to televangelism in California and house churches in China. Since the Enlightenment, intellectuals have assumed that modernization would kill religion--and that religious America is an oddity. As these authors argue, religion and modernity can thrive together, and America is becoming the norm. The failure of communism and the rise of globalism helped spark the global revival, but, above all, 21st century religion is being fueled by a very American emphasis on competition and a customer-driven approach to salvation, and its destabilizing effects can already be seen far from Iraq or the World Trade Center.--From publisher description.
Two roads to modernity. The European way : the necessity of atheism ; The American way I : the Chosen Nation (1607-1900) ; The American way II : surviving the acids of modernity (1880-2000) ; Bush, Blair, Obama and the God gap (2000-2008) -- God's country. Pray, Rabbit, pray : soulcraft and the American dream ; The God business : capitalism and the rise of religion ; Empires of the mind : God and the intellectuals -- God's empire. Exporting America's God ; All that is holy is profaned : exporting American materialism -- God's wars. The Bible versus the Koran : the battle of the books and the future of two faiths ; The new wars of religion ; The culture wars go global ; Learning to live with religion.
Includes bibliographical references (p. 376-391) and index.
Keywords: Religion and sociology; Religion and sociology -- United States; United States -- Religion